Higher categories, colimits, and the blob complex - Morrison, Scott (National Academy of Sciences, 2011)
We summarize our axioms for higher categories, and describe the “blob complex.” Fixing an n-category [Image: see text], the blob complex associates a chain complex [Image: see text] to any n-manifold W. The zeroth homology of this chain complex recovers the usual topological quantum field theory invariants of W. The higher homology groups should be viewed as generalizations of Hochschild homology (indeed, when W = S(1), they coincide). The blob complex has a very natural definition in terms of homotopy colimits along decompositions of the manifold W. We outline the important properties of the blob complex and sketch the proof of a generalization of Deligne’s conjecture on Hochschild cohomology and the little discs operad to higher dimensions.